Numerical Haemodynamics in the Human Heart - Daub, Anna Christina (Schriftenreihe des Instituts für Strömungsmechanik, Karlsruher Institut für Technologie, 2018)
The characteristic vortex formation in the ventricles is believed to be affected at an early stage of heart diseases. First, post-processing of patient-specific data has to be standardised. The chosen methods, a combination of Eulerian and Lagrangian techniques, are characterised by means of necessary spatial and temporal resolutions. Second, the goal is to find the best cost-benefit approach for modelling of the mitral valve, as it affects vortex formation and progression in the left ventricle.